Genetics of gestational trophoblastic neoplasia: an update for the clinician. (December 2010) - Alifrangis, Constantine; Seckl, Michael J
Gestational trophoblastic disease is a spectrum of disorders ranging from premalignant hydatidiform moles through to malignant invasive moles, choriocarcinoma and rare placental site trophoblastic tumor. The latter are often collectively referred to as gestational trophoblastic tumors or neoplasia (GTN). Although most women can expect to be cured of their disease, many interesting questions arise in the management of gestational trophoblastic disease. Current issues pertain to diagnosis of GTN, predicting progression from hydatidiform moles to GTN and the emergence of drug resistance in GTN. Our understanding of the genetics of GTN has helped us answer some of these questions but many remain unresolved. This article seeks to address recent advances in the genetics of GTN in relation to diagnosis, etiology, prognosis and treatment.